Mineralisation as a carbon sink for DAC: A case-study for solar thermal process integration - Dia Milani; Haftom Weldekidan; Wilson Gardner; Phillip Fawell; Robbie McDonald; Paul Feron; Michael Rae; Geoff Drewer; Graeme Puxty; Nouman Mirza; Phil Green (Cleaner Engineering and Technology)
The rising demand for critical minerals entails more greenhouse gas (GHG) emissions and increased generation of tailings and other mining wastes. This study proposes a novel process integrating concentrated solar power (CSP), accelerated mineral carbonation (AMC), and direct air capture (DAC) technologies to reduce such wastes and emissions. A closed-loop Rankine cycle generating 10 MWe electric power for a hypothetical Australian nickel mine site case-study is simulated in Aspen Plus. High temperature steam is first used in the AMC heat exchanger (AMC-HX) to provide the enthalpy for AMC before expanding in the turbine to produce the design electricity. The turbine's low-enthalpy exit steam is then used in the DAC heat exchanger (DAC-HX) as a final heat sink before condensation and pumping back to the boiler. The boiler's thermal duty is supplied by a solar central receiver system (CRS) complemented by a 10-h thermal energy storage system.For the nominal CRS design and energy balance, a net of 5.78 MJ heat per kg of carbonated product is calculated, 10 MWe electricity for mining beneficiation is maintained, while 10.7 MJ per kg of CO2 produced in DAC is also provisioned. An annual production of 175.7 kt of carbonates is predicted, permanently locking away 92.2 kt of atmospheric CO2, and reducing diesel consumption by almost 90 %. Such a design integration can bring all power-related CO2 emissions of this case-study to zero, with a further CO2 avoidance of 68.55 kt annually to offset non-power related emissions. In addition to verifying the technical and economic feasibility of such a design, a full life cycle assessment relative to business-as-usual is imperative to help in achieving the 2050 net-zero emissions target in the mining sector.